Experimental study on combustion characteristics and emission performance of 2-phenylethanol addition in a downsized gasoline engine. (15th November 2018) - Pan, Mingzhang; Wei, Haiqiao; Feng, Dengquan; Pan, Jiaying; Huang, Rong; Liao, Jinyang
Abstract: The anti-knock quality of fuels are of vital importance for improving spark ignition (SI) engine efficiency. 2-pheylethanol (2-PE) is one of potential high-octane booster, which can be derived from lignin as a biomass component. To ascertain the possibility of 2-PE as a bio-additive in SI engines, combustion characteristics and emission performance of 2-PE addition were investigated in a downsized gasoline engine. Blending 2-PE in gasoline resulted to a decrease in cylinder pressure and heat release rate. As increase of 2-PE addition, ignition delay and combustion duration of 2-PE-gasoline become postponed, combustion phasing is retarded， and COVIMEP increased signiﬁcantly. The reason is thought to be correlated with its relatively lower gas-phase reactivity and higher heat of vaporization. At elevated intake pressure, the number of knock cycles and MAPO significantly increased of SI engine，addition of 2-PE exhibits good knocking resistance because of its high octane number and physicochemical properties. For regulated gas emissions, 2-PE addition produces more unburned hydrocarbon, carbon oxide and less nitrogen oxides. The blending of 2-PE in gasoline tends to increase particle matter emissions and enlarge the particle size. Highlights: Combustion and emissions of 2-phenylethanol was studied as an octane booster. Addition of 2-phenylethanol prolonged the ignition delay and combustion duration. 2-Phenylethanol exhibited good anti-knock ability under intake boosting conditions. PM emissions increase and diameter enlarges with addition of 2-phenylethanol.